Screening of water-soluble polymer producing microorganisms for MEOR - Sugai, Yuichi; Ikeda, Shuichiro; Chida, Tadashi; Yazawa, Nintoku; Enomoto, Heiji; Hong, Chengxie (Journal of the Japanese Association for Petroleum Technology, 2002)
In order to obtain highly talented microorganisms to be applied to Fuyu oilfield, PetroChina Company Limited Jilin Oilfield Company, where fractures and sedimentary anisotropy dominate the permeability of the reservoir, microorganisms which produce water-soluble polymer were searched for Microbial FOR by means of permeability modification. Enterobacter sp. TU-7A and TRC-322 were found among talented microorganisms which had already been obtained as gas producers, and Clostridium sp. TU-15A was newly obtained. All of these three microorganisms showed the viscosity of their cultivated solution equivalent to or higher than that shown by SP018 reported by Oklahoma University. Particularly, TU-15A showed an outstanding increase of viscosity, ca. 70cP at a shear rate of 40s-1. For simulative application of strain TU-15A to Jilin oilfield, its optimal cultivation condition and dominant growth under competitive reservoir conditions were discussed. Results may be summarized as follows. 1) The viscosity of cultivated solution for TU-15A proportionally increases with the initial molasses concentration, which makes possible an estimation of economically efficient concentration of molasses for injection, and moreover, which may make possible the use of fluid of so high viscosity that its injection is impossible through a well. 2) The optimum pH range of TU-15A for polymer production is 7.0-9.0. Automatic adjustment of pH to the optimum range may be done in the reservoir of Fuyu oilfield by natural dilution with brine, the pH of which is 7.7. 3) Initial cell concentration of TU-15A in the culture solution for injection must be equal to or higher than 1.0×106 cells/ml for its dominant growth in the reservoir.